ILMU DAN AGAMA PADA KONSEPAN FILSAFAT ILMU - Dwi Ayu Damayanti,; Muhammad Nurwahidin,; Sudjarwo, Sudjarwo (Journal of Innovation Research and Knowledge, 2022)
Science is the most significant aspect of human existence so that humans can improve the quality and abilities of humans. Religion is a person's belief in something supernatural or spiritual. The method used in this study uses the literature review method. Search for articles compiled by the author through two databases, namely Garuda and Google Sholar which examines science, religion and philosophy of science. The study's findings demonstrate that, from a philosophical perspective, science and religion demonstrate that the position between the three is equal in seeking the truth.